Analisa Kelengkapan Informed Consent Tindakan Operasi di Rumah Sakit Sansani Pekanbaru - Henny Maria Ulfa (Indonesian of Health Information Management Journal (INOHIM), 2018)
AbstractInformed consent is the consent given patients told a doctor after being received an explanation. Researchers find there are still many incomplete Informed consent form. The purpose of this research is to know the analysis of the completeness of informed consent of surgery at Sansani Hospital Pekanbaru. Research methods Mixed Methods, design research Sequential Explanatory, The population all medical record of patient of surgery in 2017 were 2892, sample 97 medical record. The technique of Sampling Quota sampling, informants amounted 3 people observation, interview techniques are quantitative, qualitative analysis. The results of accuracy completeness of the informed consent has not reached 100%. Completeness of the Informed Consent Policy there has been no while the SOP and already, there's been a human resources analysis completeness with the DIII record medical degrees, the cause factor is still less awareness of the responsible officer in charge, no patient's family as witnesses, medical record officer effort is made by restoring the medical record to the room treatments. Recommends that there should be a policy and need to have monitoring, evaluation for completeness of charging medical record overall including Informed Consent so that reaches 100%.Keywords: Completeness informed consent the act of operation, medical record, the hospitalAbstrakInformed consent adalah persetujuan yang diberikan pasien kepada dokter setelah diberi penjelasan. Peneliti menemukan masih banyak formulir informed consent yang tidak lengkap. Tujuan penelitian mengetahui Analisa Kelengkapan Informed Consent Tindakan Operasi di Rumah Sakit Sansani Pekanbaru. Metode penelitian kombinasi (Mixed Methods), desain penelitian Sequential Explanatory. Populasi seluruh rekam medis pasien tindakan operasi tahun 2017 berjumlah 2892 dan jumlah sampel 97 rekam medis. Teknik pengambilan sampel Quota Sampling, informan berjumlah 3 orang dengan observasi dan wawancara. Tehnik analisis kuantitatif dan kualitatif. Hasil penelitian kelengkapan ketepatan pengisian informed consent belum mencapai 100%, Kebijakan kelengkapan Informed Consent belum ada, SOP sudah ada, sudah ada Sumber daya manusia melakukan analisa kelengkapan berlatar belakang DIII rekam medis, faktor penyebabnya kurang kesadaran petugas bertanggung jawab dalam pengisian, tidak ada keluarga pasien menjadi saksi, upaya dilakukan petugas rekam medis mengembalikan rekam medis ke ruang rawatan. Saran harus ada kebijakan, monitoring dan evaluasi untuk kelengkapan pengisian rekam medis secara keseluruhan termasuk Informed Consent sehingga mencapai 100%.Kata Kunci: Kelengkapan Informed Consent Tindakan Operasi, rekam medis, Rumah Sakit